Regional integration in Africa at the crossroads of institutionalism and transnationalism - (:unkn) unknown (My University, 2023)
Regional integration has always been at the center of African international relations. More than half a century later, the achievement of the political and economic unity of the continent remains topical. Presented as the only approach with a chance of getting Africa out of underdevelopment in a globalized world, regional integration is built both by two approaches driven by the States and by the border peoples divided anarchically by colonization. The emergence of these approaches has favored the intertwining of institutional construction and the transnational perspective in the process of building regional integration in Africa.
Keywords: African Research